2020
DOI: 10.1371/journal.pone.0225958
|View full text |Cite|
|
Sign up to set email alerts
|

Microscopic distance from tumor invasion front to serosa might be a useful predictive factor for peritoneal recurrence after curative resection of T3-gastric cancer

Abstract: BackgroundPeritoneal recurrence is one of the most frequent recurrent diseases in gastric cancer. Although the exposure of cancer cells to the serosal surface is considered a common risk factor for peritoneal recurrence, there are some cases of peritoneal recurrence without infiltration to the serosal surface even after curative surgery. This study sought to clarify the risk factors of peritoneal recurrence in the absence of invasion to the serosal surface. Materials and methodsNinety-six patients with gastric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 22 publications
(26 reference statements)
0
8
0
Order By: Relevance
“…The enhanced depth of tissue penetration of positively charged NPs after ePIPAC delivery may be clinically relevant. The tumor invasion front is located approximately 150 μm below the tumor rim in patients developing peritoneal future science group www.futuremedicine.com metastasis, whereas this front is deeper in patients without peritoneal recurrence (>300 μm) [32]. The evaluation of the clinical significance of these results will require further investigation, but it is evident that intraperitoneal drug delivery to the target tissue can be optimized by a combination of medical devices, formulation of the drug and control of the peritoneal environment.…”
Section: Discussionmentioning
confidence: 99%
“…The enhanced depth of tissue penetration of positively charged NPs after ePIPAC delivery may be clinically relevant. The tumor invasion front is located approximately 150 μm below the tumor rim in patients developing peritoneal future science group www.futuremedicine.com metastasis, whereas this front is deeper in patients without peritoneal recurrence (>300 μm) [32]. The evaluation of the clinical significance of these results will require further investigation, but it is evident that intraperitoneal drug delivery to the target tissue can be optimized by a combination of medical devices, formulation of the drug and control of the peritoneal environment.…”
Section: Discussionmentioning
confidence: 99%
“…Since most of gastric cancer cells frequently produce TGFβ [ 21 ], TGFβ from gastric cancer cells might activate Tks5 the PMCs via TGFβ-Src-Tks5 signaling. It is conceivable that peritoneal metastasis develops through direct invasion of cancer cells into the gastric wall, exfoliation of free cancer cells from the tumor to the peritoneal cavity, and adhesion to the peritoneum [ 22 , 23 ]. On the other hand, the clinical relevance of Tks5 in PMCs has not been clarified.…”
Section: Discussionmentioning
confidence: 99%
“…Our results showed that mortality was significantly higher in the patient group with lymphovascular or serosal invasion. Previous studies have shown that gastric cancer patients with serosal invasion have a higher rate of peritoneal involvement and need neoadjuvant chemoradiotherapy [20][21][22].…”
Section: Discussionmentioning
confidence: 99%